Linearitas Pernikahan Dini, Kenakalan Remaja dan Progresivitas Prevalensi Stunting - La Samudia Dalili; Priyatna Prasetyawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study focuses on strategies to prevent stunting prevalence, which to date have shown inconsistent results. Several previous studies have stated that stunting prevalence cannot be prevented optimally because it is influenced by other factors, such as early marriage and low family literacy. This study uses a qualitative approach with in-depth interview techniques with a number of key informants, including families, community leaders, and health workers. The purpose of the interviews was to gain a deeper understanding of the effectiveness of stunting prevention efforts. The research findings show that the mechanism for preventing stunting prevalence is starting to show improvement. However, these efforts will be more optimal if there is synergy between families, community institutions, and the government in providing education, especially regarding the negative impacts of early marriage. Multi-party collaboration is an important key in building collective awareness and strengthening efforts to prevent stunting sustainably.